Delayed cord clamping at delivery of a newborn-a position statement by the College of Paediatrics and the College of Obstetricians and Gynaecologists, Academy of Medicine of Malaysia - Cheah, Fook Choe; Omar, Siti Zawiah; Lim, Pei Shan; Ismail, Hamizah; Lim, C K K; Thong, Meow Keong; Yong, S C; Chee, S C (Faculty of Medicine, UKM, 2024)
Delayed cord clamping (DCC) is a practice in which the umbilical cord of a newborn is not immediately clamped and cut after birth, but deferred to allow the transfer of vital blood and nutrients from the placenta to the neonate. This position paper, in advocating DCC, highlights some key physiological factors of the newborn transitioning into extrauterine life in justifying the delay in cord clamping. The optimum timing in clamping the cord is also discussed based on the recommendations on best practice from some of the foremost international bodies involved in maternal, fetal and neonatal care. In explaining the benefits of DCC from a scientific perspective, this paper also reviews the significant impact on neonatal health, especially in decreasing intraventricular haemorrhage and circulatory instability in the preterm infant, iron deficiency anaemia, and improving long-term neurodevelopment outcome. Common concerns and potential risks related to DCC such as postpartum haemorrhage and neonatal hyperbilirubinemia are largely disproved. This position paper provides recommendations for healthcare providers and advice for parents in Malaysia, in the hope that DCC will be implemented nationwide soon as a standard of care. ***** Pengapitan tali pusat lewat (PTPL) ialah suatu amalan di mana tali pusat bayi yang baru lahir tidak segera diapit selepas kelahiran, sebaliknya ditangguhkan untuk membolehkan pemindahan darah dan nutrien yang penting dari uri ke bayi. Kenyataan pendirian ini menyokong PTPL dengan menekankan beberapa faktor fisiologi utama bayi dalam menyesuaikan diri dengan kehidupan luar rahim sebagai justifikasi untuk menangguhkan pengapitan tali pusat. Masa yang optimum untuk mengapit tali pusat juga dibincangkan berdasarkan saranan amalan terbaik daripada beberapa badan antarabangsa terkemuka yang terlibat dalam penjagaan ibu, janin dan bayi baru lahir. Dalam menjelaskan manfaat PTPL dari perspektif saintifik, kenyataan pendirian ini juga mengkaji impak signifikan terhadap kesihatan bayi baru lahir, terutamanya dalam mengurangkan pendarahan dalam otak dan ketidakstabilan peredaran darah untuk golongan bayi pramatang, anemia kekurangan zat besi, dan meningkatkan hasil perkembangan otak jangka panjang. Pada umumnya, kebimbangan dan risiko potensi yang sering dikaitkan dengan PTPL seperti pendarahan selepas bersalin dan penyakit kuning bayi baru lahir telah disangkal berdasarkan penyelidikan terkini. Kenyataan pendirian ini bertujuan memberikan saranan kepada kakitangan penjagaan kesihatan dan nasihat kepada ibu bapa di Malaysia, dengan harapan PTPL akan dilaksanakan di seluruh negara sebagai amalan piawai pada masa terdekat.